Facilitating deep-strategy behaviors and positive learning performances in science inquiry activities with a 3D experiential gaming approach. Issue 8 (17th November 2018) - Sung, Han-Yu; Hwang, Gwo-Jen; Wu, Po-Han; Lin, Dai-Qi
ABSTRACT: Facilitating students' deep-strategy behaviors and positive learning performances of science inquiry is an important and challenging educational issue. In this study, a contextual science inquiry approach is proposed for developing a 3D experiential game to cope with this problem. To evaluate the impacts of the game on students' science learning approaches, learning achievements and problem-solving awareness as well as the learning behavioral patterns of the students with different learning achievements, a quasi-experiment was conducted in an elementary school geoscience course. The participants were two classes of sixth graders. One class was the experimental group who learned with the 3D experiential game, and the other was the control group who learned with the conventional technology-enhanced learning approach. The experimental results showed that the students learning with the 3D experiential gaming system showed better learning achievements, problem-solving tendency, deep learning strategies, and deep learning motive than those who learned with the conventional technology-enhanced learning approach. Moreover, the higher-achievement students showed more behavioral patterns of deep learning strategies than the lower-achievement students. The findings of this study provide a good reference for helping lower-achievement students improve their learning performance.